The Influence of Financial Literacy and Socio-Demographics on the Financial Management Behavior of Migrant Students in Surabaya - Cynthia, Angelina; Linawati, Nanik (FKIP Universitas Lampung, 2024)
This research aims to analyze the influence of financial literacy and sociodemographic characteristics on the financial management of migrant students in Surabaya. We employed a quantitative descriptive approach and collected data through a shared Google Form. The analysis was conducted using Stata software. The results of our research reveal that a higher level of financial literacy has a positive and significant impact on the financial management abilities of migrant students. However, sociodemographic factors such as age, gender, and income do not exhibit a significant influence on their financial management. This analysis provides valuable insights into the significance of enhancing financial literacy among migrant students, thereby assisting them in improving their financial management skills.Keywords: Financial Literacy, Financial Management BehaviourDOI: http://dx.doi.org/10.23960/E3J/v7i1.13-17